(untitled) (Research, Society and Development, 2022)
Objective: This study evaluated clinical, glucose, and immunological parameters in patients with type 2 diabetes mellitus (DM) compared to those without systemic alterations (NDM), both with generalized chronic periodontitis. Methodology: Twenty-one patients were selected with indications of tooth loss. Surgeries were performed using the Widman flap modified to obtain a gingival collar at 1 mm from the gingival margin. Before the surgical procedure, the following clinical parameters were evaluated: pocket probing depth (PPD), gingival recession (GR), clinical attachment level (CAL), and bleeding on probing (BOP). Fasting glucose levels (FGL) and glycosylated hemoglobin Hba1c (HbA1c) were also assessed. During the surgery, gingival tissue samples were collected and frozen for later laboratorial analysis. The samples were processed to obtain mRNA, cDNA and determine the gene expression of the immune parameters IL-1-β, IL-6, TNF-α, IL-10 and NF-kB by real-time polymerase chain reaction (RT-PCR). Data were analyzed statistically considering p<0.05. Results: The clinical and glucose parameters BOP, FGL, and HbA1c were statistically higher in the DM group. RNAm levels of IL-1β, TNF-α, and NF-kB were higher in the DM group (p<0.05). Conclusion: The presence of diabetes and hyperglycemic status increase the levels of pro-inflammatory immune factors and severity of the periodontal disease.